(untitled) (TAMADDUN NURI JURNALI, 2024)
This article examines the comparative analysis of proverbs reflecting gender relations within English, Russian, and Uzbek cultures. Utilizing extensive statistical analyses, the study draws on a significant number of proverbs of three cultures. The findings reveal notable similarities despite the linguistic and cultural differences among these societies. In Russian and Uzbek proverbs, themes of family values and kinship prominently emerge, while English proverbs tend to celebrate and honor women and wives. Furthermore, the analysis indicates that all proverbs derive from the historical culture of their respective. Overall, the study underscores the importance of proverbs as cultural artifacts that reflect and contribute to the understanding of gender relations across different societies.